Layer-by-Layer Biopolymer-Coated Deformable Liposomes–In Situ Gel: A Hybrid Strategy for Enhanced Ocular Delivery of Itraconazole: In Vitro and In Vivo Appraisal - Mohamed M. Badran; Areej Alsubaie; Mounir M. Salem Bekhit; Abdullah H. Alomrani; Aliyah Almomen (Gels)
Itraconazole (ITZ) is a potent antifungal agent. Its oral administration is associated with systemic toxicity, and its efficacy in ocular formulations is limited. This study aims to enhance ITZ’s ocular permeation and antifungal efficacy by loading it into deformable liposomes (DLs) based on Tween 80 (T) or Poloxamer 188 (P). Moreover, ITZ was loaded into biopolymer-coated DLs to augment its ocular availability. ITZ-loaded DLs were coated with hyaluronic acid (HA-DLs), chitosan (CS-DLs), or a layer-by-layer coating (CS/HA-DLs). These formulations were further laden into pH-sensitive in situ gels to provide a hybrid system to intensify their ocular adhesion properties. The prepared DLs were successfully prepared with vesicle sizes in nonorange (<200 nm). The zeta potential values of DLS were negative before coating and shifted to high negativity with HA coating and positivity with CS and CS/HA bilayer coating. These variations of zeta potential indicate successful CS and HA coatings. The optimized A high EE% was achieved with DLs-T: 89% (CS/HA-DLs-T), 86% (CS-DLs-T), 85% (HA-DLs-T), and 79% (HA-DLs-T). Therefore, DLs-T were incorporated into in situ gels, displaying optimal gelling capacity and viscosity. The release rate of ITZ from the coated DLs-laden in situ gels was slower than that observed with the uncoated DLs-gel. CS/HA-DLs-T laden-in situ gels showed the highest ex vivo transcorneal permeability and antifungal efficacy. These data suggest that the layer-by-layer-CS/HA-DLs-T presents a hopeful strategy for the ocular delivery of ITZ, offering a promising approach for managing ocular fungal infections.